Mechanism, Machine, Robotics and Mechatronics Sciences - Rizk, Rany; Awad, Mariette (Mechanisms and Machine Science, 2019)
This volume contains the Proceedings of the First International Congress for the Advancement of Mechanism, Machine, Robotics and Mechatronics Sciences (ICAMMRMS-2017), held in Beirut, Lebanon, October 2017. The book consists of twenty papers in six different fields covering multiple angles of machine and robotics sciences: mechanical design, control, structural synthesis, vibration study, and manufacturing. This volume is of interest to mechanical as well as electrical engineers. .